KARAKTERISTIK DAN AKTIVITAS ANTIOKSIDAN PETIS AIR REBUSAN KEPALA GABUS (Channa striata) DAN TENGGIRI (Scomberomorus commersoni) DENGAN PERBEDAAN KONSENTRASI GULA KELAPA - Gemala Cahya; Ace Baehaki; Rodiana Nopianti (Jurnal FishtecH, 2014)
The objective of research was to investigate chemical and physical characteristics especially of amino acids and antioxidative activity of paste made from boiling water snakehead and mackerel head with different concentrations of coconut sugar. The research used Factorial Randomized Completely Design with 2 type of fish and 4 concentration of coconut sugar then two replicated. The treatment from types of fish (snakehead and mackerel) and concentration of coconut sugar (10%, 20%, 30%, and 40%). Parameters obsevased were chemical analysis (water content, protein content, fat content, ash content,  carbohydrates content, amino acids, and antioxidative activity), physical analysis (viscosity) and sensory testing (appearance, texture, odor and taste).  The result showed that the treatment types of fish were significant on 5% level test on water content, fat content, and carbohidrate content. The treatment  concentration of coconut sugar were significant on 5% level test affected in water content, protein content, fat content, ash content, carbohydrate content, and viscosity. But both of these treatments hadn’t effect on sensory paste. Based on SNI 01-2718-1996, the best treatment was combination of A1B1 (snakehead, 10% concentration) and A2B1 (mackarel, 10% concentration) with water content 20,85% and 20,8%, protein content 22,2% and 20,73%, fat content 7,9% and 9,7%, ash content 6,2% and 6,65%, carbohidrate 42,9% and 39,3%, viscosity 205cp and 197cp, antioxidative activity 14.028 ppm and 13,847 ppm, amino acids 7,89% and 8,93 %.